2009
DOI: 10.1016/j.ejpain.2008.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of somatostatin analogue octreotide on pain relief after major abdominal surgery

Abstract: We demonstrated that perioperative octreotide intravenous infusion could be an adjuvant to opioid analgesia as it exerted a piritramide opioid-sparing effect. We encountered more systemic side effects such as nausea, abdominal discomfort, and diarrhea in the octreotide group than in the control group. Our findings could be beneficial to patients who cannot tolerate the adverse effects of opioids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Similarly, administration of TT232, a somatostatin analog acting through peripheral SST4 receptors was devoid of significant toxicity or side effects in humans (Szolcsányi et al, 2004 ; Szokolóczi et al, 2005 ). Octreotide can alleviate pain behavior in patients (Penn et al, 1992 ; Dahaba et al, 2009 ). However, given its in vitro selectivity profile, octreotide's analgesic effect is most likely independent of SST4 receptor and more related to activation of SST2 receptor (Imhof et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, administration of TT232, a somatostatin analog acting through peripheral SST4 receptors was devoid of significant toxicity or side effects in humans (Szolcsányi et al, 2004 ; Szokolóczi et al, 2005 ). Octreotide can alleviate pain behavior in patients (Penn et al, 1992 ; Dahaba et al, 2009 ). However, given its in vitro selectivity profile, octreotide's analgesic effect is most likely independent of SST4 receptor and more related to activation of SST2 receptor (Imhof et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…It could be possible that ODT8-SST-activated oxytocin neurons play a role to counteract some stressful behavior, such as scratching since oxytocin has anxiolytic effect (Blume et al, 2008). However, it cannot be excluded that oxytocin and vasopressin are involved in other central actions of somatostatin (Legros, 2001) including analgesia (Dahaba et al, 2009) as recent evidence showed that oxytocin-induced analgesia is mediated by the vasopressin-1A receptor (Schorscher-Petcu et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…These latter have been cloned and characterized, eventually leading to the discovery of five different molecules (referred to as SSTR1‐5) that have been collected into two main families on the basis of structural and functional features (Viollet et al, 1995; Patel, 1999). The effects of SST in spinal cord are usually associated with an inhibition of nociceptive neurotransmission in several experimental paradigms (Carlton et al, 2001; Su et al, 2001; Malcangio et al, 2002), and the peptide, as well as its synthetic analogue octreotide (OCT), have been shown to evoke analgesia in many clinical situations, including several different types of pathological pain (Penn et al, 1992; Paice et al, 1996; Dahaba et al, 2009).…”
Section: Introductionmentioning
confidence: 99%